Humans and nonhumans as נֶ֥פֶשׁ חַיָּֽה and Ntu-Beings: Ecological appraisal of Genesis 2:7.19 in dialogue with African-Bantu Indigenous cosmology - Kavusa, Kivatsi Jonathan (Old Testament Essays, 2022)
The Hebrew text of Gen 2:7, 19 describes both humans and animals as nephesh hayya’ (living being). However, a large number of contemporary influential Bible translations render this expression differently for humans and animals. It is translated living being for humans (v.7), but living thing/creature for animals (v.19). This is however not justified by any clue in the text, which views humans and non-humans as both adamah-beings and nephesh hayyah. Likewise, African-Bantu cosmology depicts humans and non-humans as ntu-beings (muntu: human being; kintu: non-human being; hantu: place and time; kuntu: means or approach).The root ntu in the word kuntu implies that the way muntu (human being) interacts with other beings (kintu, hantu) must be informed by a vision of nature not as a “thing” but a living being. In addition to elements of socio-historical approaches and African-Bantu indigenous cosmology, this study makes uses of a hermeneutics of suspicion and the Earth Bible principle of mutual custodianship to retrieve ecological wisdom of Gen 2 in the African context. https://doi.org/10.17159/2312-3621/2022/v35n2a3